Psychological Safety as a Strategic Driver of Knowledge-Based Innovation in the Digital Economy - Tiara Dean Risa; Vina Varians; Muhammad Aliyandri Akbar (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study Psychological safety has emerged as a critical organizational capability that enables knowledge exchange, creativity, and innovation in the digital economy. This study aims to examine how psychological safety contributes to knowledge-based innovation by synthesizing findings from contemporary literature. Using a narrative literature review approach, this study analyzes empirical and conceptual studies published between 2022 and 2025 on psychological safety, knowledge sharing, organizational learning, employee creativity, and innovation performance. The review identifies three research questions concerning the role of psychological safety in facilitating innovation, the mechanisms linking psychological safety to innovation outcomes, and organizational strategies for strengthening innovation capability. The findings demonstrate that psychological safety encourages employees to share knowledge, express ideas without fear of negative consequences, and engage in collaborative learning, thereby enhancing creativity and innovation performance. Furthermore, knowledge sharing, organizational learning, and employee creativity operate as sequential mediating mechanisms through which psychological safety improves organizational innovation. The study also highlights that leadership support, inclusive organizational culture, digital collaboration technologies, and knowledge management systems are essential for sustaining psychological safety in increasingly digital workplaces. This review proposes an integrative conceptual framework positioning psychological safety as a strategic organizational resource that strengthens innovation capability and long-term competitiveness. The findings provide theoretical insights and practical recommendations for organizations seeking to develop resilient, knowledge-driven, and innovative workplaces in the rapidly evolving digital economy.